1996
DOI: 10.1172/jci118717
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of cyclooxygenase (COX)-2 reverses inflammation and expression of COX-2 and interleukin 6 in rat adjuvant arthritis.

Abstract: Prostaglandins formed by the cyclooxygenase (COX) enzymes are important mediators of inflammation in arthritis. The contribution of the inducible COX-2 enzyme to inflammation in rat adjuvant arthritis was evaluated by characterization of COX-2 expression in normal and arthritic paws and by pharmacological inhibition of COX-2 activity. The injection of adjuvant induced a marked edema of the hind footpads with coincident local production of PGE 2 . PG production was associated with upregulation of COX-2 mRNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
320
0
4

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 533 publications
(344 citation statements)
references
References 39 publications
20
320
0
4
Order By: Relevance
“…As the levels of TNFa and IL-1 as well as the induction of iNOS are signi®cantly lower in the plasma obtained from cloricromene-treated rats, it is not surprising that the degree of COX-2 induction is also signi®cantly attenuated in the joints of cloricromene-treated rats. There is good evidence in this and in other models of in¯ammation that an enhanced formation of prostanoids following the induction of COX-2 contributes to the pathophysiology of local and systemic in¯ammation (Salvemini et al, 1995;Anderson et al, 1996) and also that selective inhibitors of COX-2 exert potent anti-in¯ammatory e ects (Anderson et al, 1996;Mitchell et al, 1993;Harada et al, 1996).…”
Section: Discussionmentioning
confidence: 86%
“…As the levels of TNFa and IL-1 as well as the induction of iNOS are signi®cantly lower in the plasma obtained from cloricromene-treated rats, it is not surprising that the degree of COX-2 induction is also signi®cantly attenuated in the joints of cloricromene-treated rats. There is good evidence in this and in other models of in¯ammation that an enhanced formation of prostanoids following the induction of COX-2 contributes to the pathophysiology of local and systemic in¯ammation (Salvemini et al, 1995;Anderson et al, 1996) and also that selective inhibitors of COX-2 exert potent anti-in¯ammatory e ects (Anderson et al, 1996;Mitchell et al, 1993;Harada et al, 1996).…”
Section: Discussionmentioning
confidence: 86%
“…Selective COX-2 inhibitors reduce the pain and inflammation in AIA along with a corresponding decrease of PGE 2 in the inflamed paw in this model (24,25). It has recently been shown that a selective COX-1 inhibitor that does not inhibit the inflammation in AIA also does not result in inhibition of PGE 2 in the paw (26).…”
Section: Discussionmentioning
confidence: 82%
“…In preliminary experiments, the non-selective cyclooxygenase inhibitor sulindac sul®de and inhibited the proliferatioan of RIE-Tr cells in culture (data not shown). We next used a selective cyclooxygenase-2 inhibitor, SC-58125, (Seibert et al, 1994;Anderson et al, 1996;Masferrer et al, 1996) to treat the cultured cells. SC-58125 had no signi®cant e ect on growth of the RIE-1 parental cells (Figure 5a), but inhibited RIE-Tr cell growth in a concentrationa-dependent manner.…”
Section: Growth Inhibition By Inhibitors Of Prostaglandin Synthesismentioning
confidence: 99%